Genome Re-Sequencing Reveals the Host-Specific Origin of Genetic Variation in Magnaporthe Species - Li, Jinbin; Lu, Lin; Wang, Qun; Shi, Zhufeng; Li, Chengyun; Guo, Zhixiang (Frontiers in Genetics, 2022)
Rice blast is caused by the Magnaporthe oryzae (M. oryzae), which is considered as one of the most serious pathogens of rice around the globe. It causes severe losses owing to its proven capability to disrupt the host resistance. Recently, its invasion on new hosts like Musa species or banana plants has been noticed. To understand the possible level of genetic variation, we se-quenced the genomes of 8 different isolates of Magnaporthe species infecting rice, Digitaria (a weed), finger millet, Elusine indica and banana plants. Comparative genomic analysis of these 8 isolates with the previously well-characterized laboratory strain M. oryzae 70-15 was made. The infectivity of newly isolated strain from Musa species suggested that there is no resistance level in the host plants. The sequence analysis revealed that despite genome similarities, both the ba-nana and Digitaria isolates have relatively large genome size ( 38.2 and 51.1Mb, respectively) compared to laboratory reference strain M. oryzae 70-15 ( 37Mb). The gene contraction, expan-sion and InDel analysis revealed that during evolution, a higher number of gene insertions and deletions occurred in the blast fungus infecting Digitaria and banana. Furthermore, each genome shared thousands of genes, which suggests their common evolution. Overall, our analysis indi-cates that higher levels of genes insertion or deletions and gain in the total genome size are im-portant factors in disrupting the host immunity and change in host selection.